2008
DOI: 10.1080/09638280701688185
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability in disability assessment based on a semi-structured interview report

Abstract: Half the physicians thought that a reliable assessment based on the written information was possible. The quality of written patient reports made by nurse practitioners trained in conducting a semi-structured interview was considered reasonable to good by insurance physicians. The inter-rater reliability between insurance physicians of physical-disability and mental-disability assessment based on the written reports was reasonable to good. The assessment of the number hours patients could function daily had lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 11 publications
2
28
0
2
Order By: Relevance
“…Apparently the implementation strategy contributed to more uniformity in work limitations assessments by IPs. This ties in well with earlier research into variation in work disability assessments [16,17]. In terms of financial and social consequences, such variation is unwanted for both the client and society and in our opinion might be reduced by the use of standardised methods of assessment, as occurs when guidelines are applied.…”
Section: Discussionsupporting
confidence: 79%
“…Apparently the implementation strategy contributed to more uniformity in work limitations assessments by IPs. This ties in well with earlier research into variation in work disability assessments [16,17]. In terms of financial and social consequences, such variation is unwanted for both the client and society and in our opinion might be reduced by the use of standardised methods of assessment, as occurs when guidelines are applied.…”
Section: Discussionsupporting
confidence: 79%
“…psychological or cognitive symptoms) [1013]. Aspects of physical health tend to yield higher levels of patient-physician agreement as compared to aspects of mental health or well-being [14,15]. For example, one recent study reports up to a 20% discordance between patient reported anxiety and physician estimation of patient anxiety among oncology patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…When we see a patient showing a some what abnormal movement on sitting, it may not be easy to point out how and what is abnormal about it. In addi tion, the evaluation of normality may vary among in vestigators [4][5][6]. Distinguishing between normal and pathologic movements is often difficult, and it is not easy to decide what is normal for a daily movement [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although therapists observe and detect abnormal and disabled behaviors during each movement, it is not always easy to evaluate quantitative improvement/de terioration of the movement through visual observation. In addition, the reliability and variation in skill levels among therapists are marked [4][5][6].…”
Section: Introductionmentioning
confidence: 99%